Neonatal, infant and child health in South Africa: Reflecting on the past towards a better future - Goga, A; Feucht, U; Zar, H J; Vanker, A; Wiysonge, C S; McKerrow, N; Wright, C Y; Loveday, M; Odendaal, W; Ramokolo, V; Ramraj, T; Bamford, L; et al. (South African medical journal = Suid-Afrikaanse tydskrif vir geneeskunde, 2019)
Although the neonatal mortality rate in South Africa (SA) has remained stagnant at 12 deaths per 1 000 live births, the infant and under-5 mortality rates have significantly declined since peaking in 2003. Policy changes that have influenced this decline include policies to prevent vertical HIV transmission, earlier treatment of children living with HIV, expanded immunisation policies, strengthening breastfeeding practices, and health policies to contain tobacco and sugar use. The Sustainable Development Goals (2016 - 2030) have shifted the focus from keeping children alive, as expressed in the Millennium Development Goals (1990 - 2015), to achieving optimal health through the 'Survive, thrive and transform' global agenda. This paper focuses on important remaining causes of childhood mortality and morbidity in SA, specifically respiratory illness, environmental pollution, tuberculosis, malnutrition and vaccine-preventable conditions. The monitoring of maternal and child health (MCH) outcomes is crucial, and has improved in SA through both the District Health Information and Civil Registration and Vital Statistics systems, although gaps remain. Intermittent surveys and research augment the routinely collected data. However, availability and use of local data to inform quality and effectiveness of care is critical, and this requires ownership at the collection point to facilitate local redress. Potential game changers to improve MCH outcomes include mobile health and community-based interventions. In SA, improved MCH remains a crucial factor for human capital development. There is a pressing need to focus beyond childhood mortality and to ensure that each child thrives.